Structural, optical and compositional stability of MoS2 multi-layer flakes under high dose electron beam irradiation. (12th May 2016) - Rotunno, E; Fabbri, F; Cinquanta, E; Kaplan, D; Longo, M; Lazzarini, L; Molle, A; Swaminathan, V; Salviati, G
Abstract: MoS2 multi-layer flakes, exfoliated from geological molybdenite, have been exposed to high dose electron irradiation showing clear evidence of crystal lattice and stoichiometry modifications. A massive surface sulfur depletion is induced together with the consequent formation of molybdenum nanoislands. It is found that a nanometric amorphous carbon layer, unwillingly deposited during the transmission electron microscope experiments, prevents the formation of the nanoislands. In the absence of the carbon layer, the formation of molybdenum grains proceeds both on the top and bottom surfaces of the flake. If carbon is present on both the surfaces then the formation of Mo grains is completely prevented.